Time management of urban working mothers - Galilea, Maria Lourdes Enducta (2007)
This study described time management of urban working mothers in performing household tasks. Specifically, it aims to determine time spent and time-saving techniques utilized by working mothers to accomplish household tasks efficiently and conveniently. This study used a self-administered questionnaire. Purposive sampling of eighty (80) urban working mothers residing at University of the Philippines, Diliman campus was surveyed. Frequency, percentage, mean and ranking was used to analyze the data. The findings of the study revealed that urban working mothers can still manage to perform household tasks which include maintenance of home, preparation of food, laundry, shopping, budgeting, supervision and monitoring of household members, physical care of young and elderly and repair of the household appliances and furnishings. Urban working mothers spend more time in buying the everyday needs of the family. The respondents of the study also indicated the value of using of labor-saving devices, sharing of household chores by family members and following a plan or schedule of activities in order to save time and energy.